Isolation of Klebsiella pneumoniae from water and hand swabs of vegetable vendors collected from the wet markets of Dhaka city - Zaman, Afsana; Labiba, Mashiat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2024.